SISTEM PENYIMPANAN BAHAN MAKANAN DI TOM’S CAFE TEMBILAHAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Sarni "; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Cafe is a place where everyone can enjoy it, whether to eat, drink or to relax. To support it is necessary to have a menu provided from the cafe so that visitors can relax while enjoying the food and drinks available. With the existence of food and beverages then the need for foodstuffs that will be processed so that requires a storage area that must be in accordance with foodstuffs that will be stored, with the storage area it must be done food storage system so that the food becomes more durable and can last long with The quality is still good. This study aims to determine the existing food storage system in Tom's Cafe Tembilahan. The research method used in this research is quantitative approach method, the informant of this research is one person key informant as manejer Tom's Cafe and there are three additional informant. Data collection is done by using interview, observation and documentation. The results showed that in the existing food storage system in Tom's Cafe is good this is in accordance with what is expressed by key infomation through interviews and documentation.Keywords : Cafe, Storage Materials, Foodstuffs and Food Storage Systems